Implementasi Metode Konvensional Pada Pembelajaran Sejarah Kebudayaan Islam di PP. Darunnajah Al-Barokah Bengkulu - Pangestuti, Ruli Aulia; Afriansyah, Jefri; Alimni (JPT : Jurnal Pendidikan Tematik, 2020)
The purpose of this study was to determine the implementation of conventional methods in learning the history of Islamic culture in PP. Darunnajah Al-Barokah. This type of research uses a qualitative approach with descriptive methods. Data analysis using data reduction steps, displaying data and drawing conclusions by collecting data using observation, interviews, and documentation. Darunnajah Al-Barokah, so students seem bored and boring. The History of Islamic Culture is a story of the past which is the result of creation, work and human initiative guided by Islamic teachings. Learning the history of Islamic culture is very important because by understanding history properly and correctly, Muslims can reflect to take many lessons and correct deficiencies or mistakes in order to achieve glory and glory in this world and the hereafter. However, students in PP. Darunnajah Al-Barokah uses conventional learning methods, there are still many students who do not understand the material explained by the teacher. Students who do not understand the history of Islamic culture learning are 80% of the 30 students, and only 20% of the students already understand.